Olimpíada de língua portuguesa : um diagnóstico com foco nos alunos - Silva, Elisangela Maria da (2010)
In the contemporaneous world with the advent of technologies, the rapid communication and the emergence of emerging textual genre, it increases the necessity for continuous training of teachers. In this context, it s comes from Portuguese language s Olympic as a further opportunity to improve the quality of education. Realized that the work s proposal in the Mother Tongue based on the statement and their production conditions for understanding and producing well done texts. Research suggests investigating, from the learner s productions, the effects of the didactic sequence presented by the Portuguese language s Olympic, as well as the interaction s situations during the implementation process of the workshops. The research context was developed by a State Public School of elementary school in the Municipality of the Ipojuca, in which data were collected: a) through the production of a first text, b) implementation of the didactic sequence (workshops), and c) production of a final text with students of the 8th grade of elementary school. This research was based on a perspective of teaching-learning social interactionist discursive in Bakhtin (2003) and Marcuschi s (2008) concept of textual genre, In the Adam s concept of typology (Apud BRONCKART, 2003), in the Moses (2008) Genette (1995) and Gancho s (2006) concept of literary genres. It s been adopted the work s proposal with textual genres made by Schneuwly & Dolz (2010) and the Bosi (2003), Halbwachs (2006) and Pollak s (1989) sociological aspects. The research attempted to verify: a) what the students already knew about the genre Memories literary - initial production, b) the resulted after implementation of the didactic sequence - final production and c) the interactions exist in this process. Data analysis showed whom the students proved more able to produce narratives of memory after the didactic sequence, since it allowed the student to observe the language usages and unusual ways of written and oral communication, in addition to accomplish in the comprehension, production and textual analysis context the language work